Understanding drugs : heroin - Godfrey, Marin; West, David; Parker, Steve; Weston-Baker, Cecilia; Harper, Peter (New York, United States : Franklin Watts, 1987)
Each title gives clear information about particular drugs wthat they are, where they come from, and their effects on both mental and physical health.
Contents Introduction Why do people take Heroin? What does Heroin do? Illnesses that Herion brings The cost of addiction y otros más....
Incluye Index
Keywords: DRUGS -- HEROIN